TEORI BEBAN KOGNITIF: ELEMEN INTERAKTIVITAS DALAM PEMBELAJARAN MATEMATIKA - Barep Yohanes; Rendi Lusbiantoro (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2019)
This study aims to describe the emergence of Elements of Interactivity on the intrinsic cognitive load of students in mathematics learning. The approach in this study is a qualitative approach and this type of research is descriptive research. Data obtained in this study include qualitative data obtained from observation sheets, student learning journals, interviews, and video recordings. To check the validity of the data using the triangulation method and the strategy presents different or negative information. The subjects in this study were students of class X RPL 3 of TELKOM Vocational School Malang. The results of the study obtained that the Element of Interactivity is part of the intrinsic cognitive load that arises in learning. Interactivity elements that appear in learning can be seen from the complexity of the material being studied so that students must connect between material topics where the points, lines, fields and topics of material distance and the angles in building space. The complexity of the material being studied also involves prerequisite material such as the congruence of two triangles, algebra, special angles and the students' expertise in learning mathematics. Suggestions can be given from the researcher that in learning it is necessary to pay attention to the element of interactivity to find out the burden carried out by the cognitive students. The teacher must always evaluate students' abilities so that students are not too heavy in learning.